2020
DOI: 10.1002/btpr.3074
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy integration to miniature bioreactors and large scale production bioreactors–Increasing current capabilities and model transfer

Abstract: Spectroscopy techniques are being implemented within the biopharmaceutical industry due to their non-destructive ability to measure multiple analytes simultaneously, however, minimal work has been applied focussing on their application at small scale. Miniature bioreactor systems are being applied across the industry for cell line development as they offer a high-throughput solution for screening and process optimization. The application of small volume, high-throughput, automated analyses to miniature bioreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…The good model performance of glucose agrees with previous findings with a similar spectrometer/probe/measurement chamber combination, which was integrated into an Ambr®15 system ( Rowland-Jones et al, 2020 ). The in-line application of a Raman probe into the cell-free harvest stream of a perfusion process allowed for an excellent signal to noise ratio as no cells (i.e., scattering particles) are present in the sample.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The good model performance of glucose agrees with previous findings with a similar spectrometer/probe/measurement chamber combination, which was integrated into an Ambr®15 system ( Rowland-Jones et al, 2020 ). The in-line application of a Raman probe into the cell-free harvest stream of a perfusion process allowed for an excellent signal to noise ratio as no cells (i.e., scattering particles) are present in the sample.…”
Section: Resultssupporting
confidence: 87%
“…First, the concentration range is relatively low. Experience gathered in previous trials has shown that at least ten times the model error (of a valid model) is needed for model building, so at least 2 g/L ( Rowland-Jones et al, 2020 ). Second, most data-points are roughly between 0.4 g/L and 0.6 g/L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementations of PLS regression used for the online monitoring and control of bioprocesses in stirred tank reactors are numerous and have extensively been reviewed in the literature [ 26 , 39 , 40 ]. Yet, to date, the means for the online recording of high-dimensional data in microbioreactors are limited, and applications of PLS modelling are mostly based on spectral at-line measurements [ 19 , 20 , 41 , 42 , 43 ]. Recently, Sawatzki et al [ 44 ] used PLS regression to predict the endopolygalacturonase activity during fed-batch cultivations of Saccharomyces cerevisiae in 8–12 mL stirred cultures.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Furthermore, a miniatured bioreactor system allowing up to 48 simultaneous cultivations at different conditions was shown to facilitate Raman model calibration for reliable glucose and lactate predictions. [14] Spiking strategies to augment analyte variability in the calibration data set were demonstrated in situ, [12,15] at-line, [16] and offline. [17] In contrast to the standard cali- of product titer in perfusion harvest using a stainless-steel flow cell was used to optimize an integrated continuous chromatography step, [18] whereas others developed a more sophisticated flow cell intensifying Raman signals to detect product breakthrough in a continuous protein A capture step.…”
Section: Introductionmentioning
confidence: 99%